Chronic and Gradual-Onset Injuries and Conditions in the Sport of Surfing: A Systematic Review - Samuel Hanchard; Ashley Duncan; James Furness; Vini Simas; Mike Climstein; Kevin Kemp-Smith (MDPI AG, 2021)
The majority of the previous literature investigating injuries in surfing have focused on acute or traumatic injuries. This systematic review appears to be the first to investigate the literature reporting on chronic and gradual-onset injuries and conditions in surfing populations. A search strategy was implemented on five databases in June 2020 to locate peer-reviewed epidemiological studies on musculoskeletal injuries or non-musculoskeletal conditions in surfing. A modified AXIS Critical Appraisal Tool was used to appraise all included texts. Extracted data included key information relevant to the epidemiology of the injuries and conditions. Twenty journal articles were included with the majority rated as good quality and a substantial agreement between raters (k = 0.724). Spine/back (29.3%), shoulder (22.9%), and head/face/neck (17.5%) were the most frequently reported locations of musculoskeletal injury, whilst the most common mechanism of injury was paddling (37.1%). Exostosis was the most frequently described injury or condition in surfing populations, with the most common grade of severity reported as mild obstruction. The key findings of injury type, location, severity, and mechanism can be used to develop relevant injury management and prevention programs for the surfing population, with an emphasis on chronic or gradual-onset spine/back and shoulder injuries, paddling technique, and education on the development and management of exostosis.